Financial development, growth and equity in Brazil - Armando Castelar Pinheiro; Régis Bonelli (Institute for Applied Economic Research (ipea), 2015)
Financial markets help to foster growth and productivity through their role in mobilizing savings to finance investment and production, selecting and monitoring investment projects, diversifying risks, and allowing investment and production to be carried out in the most productive scale and time frame. This paper examines the links between financial development, growth and equity. The focus is on the Brazilian case, but we also aim at contributing to a broader discussion on the role of financial markets in fostering economic development in Latin America. The analysis discusses: a) Brazil's recent growth record, which resembles Latin America's average regarding pace and sources of growth; b) recent changes in financial intermediation in the region, stressing the role of the public sector in absorbing private savings; c) the interface between growth and finance; d) the issue of access to financial services; and e) the impediments to financial deepening and inclusion drawn from the Brazilian experience. Among its conclusions we highlight the relatively small contribution the Brazilian financial system has had towards promoting growth and equity in the following sequence: a) the incomplete macroeconomic adjustment of the economy, which lead to high interest rates, market volatility, and a preference of savers for liquid, short-term financial investments; b) the high tax burden and the associated high degree of informality and fiddling with company accounts, which lower the quality of the information disclosed to financial institutions and capital markets; c) the central role of the state in mobilizing and allocating savings, largely an inheritance of the pre-1990s development model, which dampens the impact of financial intermediation on capital productivity; and d ) the low protection of minority shareholders and especially creditors against expropriation by the state and private parties create a highly uncertain and risky environment that raises the cost of capital, discourages financial intermediation and raises the preference for short-term and liquid financial assets.
Keywords: E44; G20; O16; 330